Near Surface Geophysics - Near Surface Geophysics (Wiley, 2026)
Near Surface Geophysics is an international journal for the publication of research and development in geophysics applied to the near surface. The emphasis lies on shallow land and marine geophysical investigations addressing challenges in geology, hydrogeology, environmental science, civil and geotechnical engineering, agriculture, archaeology, mining and mineral exploration, geohazards, the influence of climate change, exploration, and storage of energy (incl. geothermal, wind and other renewables), and near-surface soil- and rock-physical properties. Geophysical and geoscientific case histories with innovative use of geophysical techniques are welcome, which may include improvements in instrumentation, measurements, data acquisition and processing, modelling, inversion, interpretation, integration, project management, and multidisciplinary use. The papers should also be understandable to those who use geophysical data but are not necessarily geophysicists.
FI 0.41
Q3
Keywords: Earth; Space & Environmental Sciences; Geophysics; Acuerdos transformativos; Transformative agreements; Geofísica somera; Subsuelo superficial; Métodos geofísicos; Caracterización del subsuelo